Tipografi yang Digunakan Dalam Perancangan Picture Book Berjudul Raja Burung Parakeet - Brata, Mathius Wishnu (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study aims to evaluate the effectiveness of the OpenDyslexic font in helping children aged 7-8 years learn to read. The experimental method involved two groups of students; one group used reading materials in the OpenDyslexic font, and the other group used the standard font. Data were collected through reading tests that measured speed and comprehension before and after the intervention. This design uses the Design Thinking method with data collection techniques, namely interviews and literature study. Results showed that children with reading difficulties who used the OpenDyslexic font experienced significant improvements in reading speed and comprehension compared to the control group. The OpenDyslexic font, with letter shapes specifically designed to facilitate reading by normal children and children who have difficulty reading, helps children recognize letters and words more easily. In conclusion, the use of the OpenDyslexic font is effective in helping children learn to read and can be used as an alternative in teaching materials to improve early childhood literacy. It is hoped that this research will be able to provide solutions for children who have obstacles in learning to read, besides that it can be used as a relevant reference source.